Real-time implementation of a fuzzy inference system for banana grading using DSP TMS320C6713 platform - Mustafa N.B.A.; Gandi S.; Sharrif Z.A.Md.; Ahmed S.K. (2023)
Fuzzy Logic theory has been applied in various fields and technologies. One of the Fuzzy Logic application is to grade the agriculture produce based on its size. Currently, the grading is done based on observations and through experience. For further improvement, a high speed grading system using a Fuzzy Inference System is designed to grade the agriculture produce. In this research, a banana fruit was chosen to show the viability of this system. The Fuzzy Inference System grades a banana based on the extracted features that are obtained using Image Processing techniques of several images of each fruit. Since, this grading process requires a high speed processor, a typical computer platform is not a perfect choice. Therefore in this paper, we design and implement a grading system that uses a high speed digital signal processor. Hence, DSP TMS320C6713 was chosen for the implementation process. This paper discusses the implementation process of a fuzzy logic program on DSP TMS320C6713 platform. 2010 lEEE.